Quadrupolar fluorophores with tetrafluorobenzene central electron acceptor - Kulhánek, Jiří; Klikar, Milan; Pytela, Oldřich; Al Monasy, Numan; Tydlitát, Jiří; Bureš, Filip (Elsevier Science SA, 2021)
Seven novel quadrupolar chromophores based on 1,2,4,5-tetrafluorobenzene (TFB) central electron acceptor unit and methoxythiophene peripheral donor were synthetized and described. Fundamental structure-property relationships were elucidated via thermal, electrochemical and optical measurements. These revealed that the properties are mostly affected by the used p-linker. Variation of the p-linker resulted in tuning of the HOMO-LUMO gap. The LUMO clearly reflects planarity, polarizability and electronic transparency of the utilized p-linker. The absorption maxima of target chromophores were found within the range of 346-412 nm and the emission maxima of emissive derivatives were found within the range of 411-499 nm. Novel TFBs were compared with TFBs previously described in the literature. The experimental data are further corroborated by theoretical calculations.
Quadrupolaární fluorofory s tetrafluorbenzenem jako centrálním elektronakceptorem
Keywords: tetrafluorobenzene; methoxythiophene; push-pull chromophore; fluorescence; tetrafluorbenzen; methoxythiofen; push-pull chromofor; fluorescence